2019
DOI: 10.1159/000502156
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Expert Recommendation for Diagnosis and Treatment of Massive Hemoptysis

Abstract: Massive hemoptysis is one of emergency and critical diseases of the respiratory system. The definition of massive hemoptysis has always been different in the literature, which often depends on the quantitative estimation of the amount of hemoptysis, such as the amount of hemoptysis being in the range of 300–600 mL within 24 h, or hemoptysis more than 3 times within 1 week. Each amount of hemoptysis that is greater than 100 mL can be considered as massive hemoptysis, but the amount of hemoptysis is difficult to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 45 publications
0
33
0
Order By: Relevance
“…Medical records of 126 consecutive BE patients without mycobacterial or fungal infection who underwent BAE at the NHO Tokyo National Hospital between January 2011 and December 2018 were retrospectively reviewed. BAE was performed in patients with episodes of massive or non-massive but recurrent haemoptysis [1, 6]. Massive haemoptysis was defined as bloody expectoration estimated to be >300 mL within 24 h [6].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Medical records of 126 consecutive BE patients without mycobacterial or fungal infection who underwent BAE at the NHO Tokyo National Hospital between January 2011 and December 2018 were retrospectively reviewed. BAE was performed in patients with episodes of massive or non-massive but recurrent haemoptysis [1, 6]. Massive haemoptysis was defined as bloody expectoration estimated to be >300 mL within 24 h [6].…”
Section: Methodsmentioning
confidence: 99%
“…Haemoptysis is defined as the expectoration of blood from the lungs or bronchial tree and, due to asphyxia and blood loss, is a life-threatening symptom [1, 2]. Haemoptysis can also impair patient’s quality of life [3-5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PVS is defi ned as ≥20% luminal narrowing of PVs. [3] Jin et al [10] reported that when venous pressure suddenly rose for some reason, the venous dilatation or varicose formation caused by elevated pulmonary venous pressure may trigger rupture. Histological examination of PVS in patients after RFCA shows obviously thickened vein walls resulting in cardiomyocyte death followed by myofi broblast proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant animal experiments also confirmed that Hemocoagulase agkistrodon does not affect the number of prothrombin and platelets in the blood, and there is no platelet aggregation in normal blood vessels. Therefore, Hemocoagulase agkistrodon is not easy to cause thrombosis in normal blood vessels [19]. In this study, the method of preoperative intravenous administration was used to observe the effect of Hemocoagulase agkistrodon in spinal surgery.…”
Section: Discussionmentioning
confidence: 99%